DATA CENTERS IN THE REPUBLIC OF KAZAKHSTAN: FEATURES OF THE LEGAL STATUS AS SUBJECTS OF CIVIL LAW RELATIONS (Journal of actual problems of jurisprudence, 2025)
In the context of rapid digitalization of the economy and society, data centers (DCs) play a key role in ensuring the storage, processing, and transmission of information. This article is devoted to the study of the legal status of data centers in the Republic of Kazakhstan within the framework of civil law relations. The legal and regulatory framework governing the activities of data centers is analyzed, including the Law of the Republic of Kazakhstan "On Informatization", the Law "On Personal Data and Their Protection", as well as subordinate acts that establish requirements for the operation of data centers. Special attention is given to the question of whether data centers can be considered subjects of law or merely objects of property relations. The article also provides a comparative overview of international practices (EU, USA, Russia), which makes it possible to identify common and distinctive features of national regulation. Based on the results of the research, conclusions and proposals are formulated for improving the legal status of data centers in Kazakhstan.Keywords: data centers, legal status, subjects of civil legal relations, digital infrastructure, data center regulation, information technologies, international experience